DEVELOPMENT OF WORDWALL INTERACTIVE TECHNOLOGY TO IMPROVE ARABIC VOCABULARY AT AL-MAAHIRA IIBS JUNIOR HIGH SCHOOL MALANG - Makfiro, Nikmatul; Pelealu, Nanda Dzikrillah; Wicaksono, Meidias Abror; Machmudah, Umi; Kader, Muhammed Yahya (Universitas Negeri Semarang, 2025)
This study aims to develop Arabic vocabulary learning media based on Wordwall application using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). This research was conducted at Al-Mahiraa IIBS Malang Junior High School involving seventh grade students as subjects. The analysis stage identifies learning needs and student characteristics, while the design and development stage produces interactive game-based learning media such as Speaking Cards, Matchmaker and Quiz. Validation by media experts and material experts showed a very high level of feasibility with an average score of 87.1%. The implementation in the classroom shows that Wordwall is effective in improving students' vocabulary understanding, as well as creating an interactive and fun learning atmosphere. Then the evaluation shows a positive response from students with an average percentage of 86%, although there are technical problems such as errors in the program. In conclusion, Wordwall media is proven effective and feasible to be applied in Arabic language learning, but still requires further development to optimize its use.